2008
DOI: 10.1086/592236
|View full text |Cite
|
Sign up to set email alerts
|

NGC 602 Environment, Kinematics and Origins

Abstract: The young star cluster NGC 602 and its associated HII region, N90, formed in a relatively isolated and diffuse environment in the Wing of the Small Magellanic Cloud. Its isolation from other regions of massive star formation and the relatively simple surrounding HI shell structure allows us to constrain the processes that may have led to its formation and to study conditions leading to massive star formation. We use images from Hubble Space Telescope and high resolution echelle spectrographic data from the Ang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 21 publications
3
45
0
Order By: Relevance
“…Using the shell catalog derived from the 21 cm neutral hydrogen (Hi) spectrum survey data (Staveley-Smith et al 1997;Staminirovíc et al 1999) we identified a distinct Hi cloud component that is likely the progenitor cloud of the cluster and the Hii region which probably formed in blister fashion from the cloud's periphery. A comparison between Hi and Hii kinematics suggests that star formation in NGC 602 was triggered by compression and turbulence associated with Hi shell interaction ∼ 7 Myr ago (Nigra et al 2008).…”
Section: Ngc 602 Kinematicsmentioning
confidence: 99%
“…Using the shell catalog derived from the 21 cm neutral hydrogen (Hi) spectrum survey data (Staveley-Smith et al 1997;Staminirovíc et al 1999) we identified a distinct Hi cloud component that is likely the progenitor cloud of the cluster and the Hii region which probably formed in blister fashion from the cloud's periphery. A comparison between Hi and Hii kinematics suggests that star formation in NGC 602 was triggered by compression and turbulence associated with Hi shell interaction ∼ 7 Myr ago (Nigra et al 2008).…”
Section: Ngc 602 Kinematicsmentioning
confidence: 99%
“…A natural mechanism for assembling the large amounts of gas necessary for the formation of molecular clouds is from large-scale converging atomic flows, such as expanding shells (Elmegreen & Lada 1977;McCray & Kafatos 1987), colliding shells (Nigra et al 2008), or flows generated by large-scale gravitational instabilities (Yang et al 2007;Kim & Ostriker 2002, 2006. Gas in these collision environments is subject to a number of fluid instabilities that can cool and condense it enough for it to become molecular (Heitsch et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the morphology of this association is reminiscent of an expanding bubble of gas, UCLES high-resolution spectra show very low velocity dispersion, excluding large-scale motions (Nigra et al 2008). Another possible explanation for the NGC 602 morphology is that we are observing a cavity eroded by the OB UV stellar radiation.…”
Section: Ngc 346mentioning
confidence: 91%
“…The SMC youngest star clusters 249 formation in NGC 602 was triggered by compression and turbulence associated with H i shell interaction ∼ 7 Myr ago (Nigra et al 2008).…”
mentioning
confidence: 99%